The Effect of the Presumption of Fault in Administrative Penal Law on the Presumption of Innocence - Minshawy, Mohamad Ahmad (Journal of Legal Studies and Researches, 2017)
The Administrative Penal Code emerged as a result of the efforts of legislators who sought to put the grounds for administrative sanctions. In many countries, the legislators tried to combat certain crimes through administrative sanctions such as the fine or some of other measures. The legislator has put in some countries, what is known formally administrative sanctions law other than the Egyptian and Arab legislator, although he used the administrative sanctions in a lot of places as a punishment of administrative closure and withdrawal of the license ... and the like.